Congestion effects on regional & system emission and consumers allocated cost - Pourakbari-Kasmaei, M. [UNESP]; Rider, M. J. [UNESP]; Mantovani, J. R.S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper considers the congestion effects on emission and consumers' allocated cost. In order to consider some environmental and operational effects of congestion, an environmental constrained active-reactive optimal power flow (AROPF) considering capability curve is presented. On outage conditions, the total cost of the system will increase. On the other hand in power systems, the operating cost and system emission have conflicted objectives, then it may be concluded that the outage in the system may lead to a total emission decrease. In this paper the famous Aumann-Shapley method is used as a pricing methodology. Two case studies such as 14-bus and 118-bus IEEE test systems are conducted. Results demonstrate that, although the line outage in power systems leads to increase the total cost, the amount of emission depending on the place where the outage occurs can be more than, less than or equal to the normal conditions' emission. Also results show that although from power sellers' standpoint the well-known Aumann-Shapley method is a precise pricing method to cover the incurred cost with an acceptable error that can show the real effect of congestion on consumers' cost, from consumers' standpoint it is not a good method for cost allocation, because some consumers will face with an increase in cost and the others will face with a decrease on their cost. © 2013 IEEE.
Keywords: active-reactive OPF; Aumann-Shapley pricing; congestion; regional emission limit; system emission limit